2008
DOI: 10.1002/ana.21229
|View full text |Cite
|
Sign up to set email alerts
|

Bumetanide enhances phenobarbital efficacy in a neonatal seizure model

Abstract: Thus, alteration of Cl- transport by bumetanide enables the anticonvulsant action of phenobarbital in immature brain. This is a mechanistic demonstration of rational anticonvulsant polypharmacy. The combination of these agents may comprise an effective therapy for early-life seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
245
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(257 citation statements)
references
References 82 publications
11
245
1
Order By: Relevance
“…4B) ( P = 0.86, 0.8, and 0.25, respectively, n = 5). Interseizure interval tends to gradually decrease in this preparation over time,36 but celecoxib did not revert this trend (Fig. 4B).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…4B) ( P = 0.86, 0.8, and 0.25, respectively, n = 5). Interseizure interval tends to gradually decrease in this preparation over time,36 but celecoxib did not revert this trend (Fig. 4B).…”
Section: Resultsmentioning
confidence: 84%
“…Extracellular field potentials were recorded in the CA1 and/or CA3 pyramidal cell layer of intact hippocampi36 and organotypic hippocampal slices in a conventional submerged chamber using tungsten‐coated microelectrodes and ISO‐DAM8A amplifier (World Precision Instruments). Oxygenated (95% O 2 and 5% CO 2 ) artificial cerebrospinal fluid containing 126 mmol/L NaCl, 3.5 mmol/L KCl, 2 mmol/L CaCl 2 , 1.3 mmol/L MgCl 2 , 25 mmol/L NaHCO 3 , 1.2 mmol/L NaH 2 PO 4 , and 11 mmol/L glucose (pH 7.4), was continuously perfused at 33 ± 0.5°C.…”
Section: Methodsmentioning
confidence: 99%
“…Another study found bumetainde to enhance the anticonvulsant action of phenobarbitone in immature brain by alteration of Cl-transport. Seizures were abolished in 70% and significantly reduced the frequency, duration and power of seizures in the remaining 30% when both drugs used in conjunction (106) .…”
Section: Neonatal Seizures 39mentioning
confidence: 99%
“…As a result, during early stages of development, the GABA-A receptor-mediated opening of Cl -channels leads to an outward Cl -flow and, thus, to excitation [122]. One of the presumed consequences of GABA acting as an excitatory neurotransmitter early in life is the ineffectiveness of GABAergic antiepileptic drugs [122,123] on the one hand, and the antiepileptic effects of NKCC1 blockers on the other hand. Indeed, the NKCC1 blocker bumetanide exerted acute anticonvulsant effects in immature animals [123].…”
Section: Rapid Kindling: a Model Of Epileptogenesis In The Developingmentioning
confidence: 99%
“…One of the presumed consequences of GABA acting as an excitatory neurotransmitter early in life is the ineffectiveness of GABAergic antiepileptic drugs [122,123] on the one hand, and the antiepileptic effects of NKCC1 blockers on the other hand. Indeed, the NKCC1 blocker bumetanide exerted acute anticonvulsant effects in immature animals [123]. Under conditions of rapid kindling applied to immature animals across different ages, bumetanide exerted potent antiepileptogenic effect in all but few neonatal rats, yet it was completely ineffective in pre-adolescent subjects.…”
Section: Rapid Kindling: a Model Of Epileptogenesis In The Developingmentioning
confidence: 99%